Cyberchondria, Covid-19 phobia, and well-being: a relational study on teachers - Karakaş, Neşe; Tekin, Çiğdem; Bentli, Recep; Demir, Ekrem (La Medicina del Lavoro, 2022)
Background: This study aims at investigating level and contributor factors of Cyberchondria, Covid-19-related Phobia, and Well-Being in a sample of teachers in Turkey. Methods: The study was conducted on teachers (n=1000) working in a province in eastern Turkey. Data for the study were collected using a form that included participants’ descriptive characteristics, the Covid-19 Phobia Scale (C19P-SE), the Cyberchondria Severity Scale, and the World Health Organization-5 Well-Being Index (WHO-5). Spearman correlation analysis, Mann-Whitney U test, and Kruskal Wallis analysis of variance were used to analyze the data. Results: As participant’s cyberchondria levels rose, C19P-SE scores increased (r=0.271, p<0.001), and WHO-5 scores decreased (r=-0.224, p<0.05). Corona-phobia was higher in those who used social media than in those who did not (p<0.05). Cyberchondria scale scores were higher among those who had taken medications without a physician’s recommendation during the pandemic. Participants who had a disabled person or a person in need of care in their household had higher scores for distrust of the physician and C19P-SE than for the cyberchondria severity scale sub-dimension, and the WHO-5 mean scores were lower (p<0.001, P=0.016, and P=0.020, respectively).Conclusions: The study results show that increasing levels of cyberchondria trigger Covid-19 phobias in teachers during the Covid-19 pandemic and negatively affect their well-being. This descriptive study can help understand the risk group for cyberchondria, the influencing factors, and the health and economic consequences, and identify strategies for effective combating with cyberchondria.